A Case of Atazanavir Urolithiasis Diagnosed by Stone Analysis - Noma, Yasuhiro (Hinyokika kiyo. Acta urologica Japonica, 2016)
A 70-year-old man was referred to our hospital for right back pain. His past history included human immunodeficiency virus infection, which had been treated with atazanavir for 7 years. Abdominal and pelvic computed tomographic scan showed right hydronephrosis due to a strongly suspected right ureteral radiolucent stone. He underwent indwelling of a right ureteral stent because of obstructive pyelonephritis due to the ureteral stone. After improvement of the pyelonephritis, he underwent transurethral ureterolithotripsy for the right ureteral stone. Stone analysis showed the atazanavir stone. He has been followed up for 8 months without evidence of recurrence. Herein, we report this rare case of an atazanavir stone in Japan, which was confirmed by calculus analysis, and present a review of the literature